The effect of high-pressure on organocatalyzed ROP of γ-butyrolactone. (26th October 2021) - Bernat, Roksana; Maksym, Paulina; Tarnacka, Magdalena; Koperwas, Kajetan; Knapik-Kowalczuk, Justyna; Malarz, Katarzyna; Mrozek-Wilczkiewicz, Anna; Dzienia, Andrzej; Biela, Tadeusz; Turczyn, Roman; Orszulak, Luiza; Hachuła, Barbara; et al.
Abstract: In this paper, we report 1, 5, 7-Triazabicyclo[4.4.0]dec-5-ene (TBD) supported high-pressure approach enforcing Ring-Opening Polymerization (ROP) of γ-butyrolactone (GBL), that due to unfavorable thermodynamics and low ring strain, is considered as a hardly polymerizable monomer. Application of Broadband Dielectric Spectroscopy (BDS) allowed us to find optimal thermodynamic conditions to perform well-controlled and notably fast polymerization (even within 1 h!), avoiding undesired crystallization process. It was shown that by varying pressure and temperature conditions, we could control molecular weight, dispersity of recovered macromolecules, as well as rate and efficiency of the reaction that are significantly altered with respect to the reference process carried out at ambient conditions. Experiments performed at respectively very low temperature T = 233 K and low/moderate pressure ( p = 75–250 MPa) and much higher temperatures ( T = 248–268 K) and compressions ( p = 1000 MPa) yielded poly(γ-butyrolactone) (PGBL) of tailored absolute molecular weight in moderate range M n = 2.8–15.0 (up to 30.3) kg/mol and narrow/moderate dispersity ranging from Đ = 1.12–1.89. What is more, the implementation of MALDI-TOF, GPC and DSC analyses, clearly indicated that as i) the time of reaction gets longer, ii) the amount of catalyst increases, iii) the temperature lowers, the content of cyclic products in produced polymers grows. This phenomenon influences the rheological properties (viscosity), foil formation ability (films) and cell culture proliferation features of the recovered macromolecules. Presented results open a highly effective and repeatable route to produce PGBL via pressure-assisted ROP and indicate the possibility of tuning properties of this polymer by varying concentration of cycles or eventual block copolymerization with other biorelevant monomers to meet the expectations of the biotechnological industry. Graphical abstract: Image 1 Highlights: Organocatalyzed high-pressure assisted γ-butyrolactone Ring-Opening Polymerization. Well-defined macromolecules ( M n up to 30.3 kg/mol; low to moderate Đ = 1.12–1.89). External catalytic effect of high pressure: reduced reaction time; increased yield. Monitoring the polymerization progress in situ using BDS technique. Analysis: NMR, GPC, MALDI, DSC, SEM, rheology, cytotoxicity, cell proliferation.